2014
DOI: 10.1021/nl500008y
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Core/Semiconductor-Shell Nanocones for Broadband Solar Absorption Enhancement

Abstract: Nanostructure-based photovoltaic devices have exhibited several advantages, such as reduced reflection, extraordinary light trapping, and so forth. In particular, semiconductor nanostructures provide optical modes that have strong dependence on the size and geometry. Metallic nanostructures also attract a lot of attention because of the appealing plasmonic effect on the near-field enhancement. In this study, we propose a novel design, the metal-core/semiconductor-shell nanocones with the core radius varying in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(96 citation statements)
references
References 32 publications
2
93
1
Order By: Relevance
“…[ 17,18 ] Although nanopyramid structures have been used to enhance the absorption of c-Si or GaAs solar cells in the solar spectrum above the electronic bandgaps of the semiconductors, [19][20][21] generally, selective solar absorption and high-temperature stability are not required for solar cells. In addition, fabrication of nanopyramid structures onto solar cells is usually expensive, and diffi cult to be scaled up.…”
Section: Doi: 101002/adma201501686mentioning
confidence: 99%
“…[ 17,18 ] Although nanopyramid structures have been used to enhance the absorption of c-Si or GaAs solar cells in the solar spectrum above the electronic bandgaps of the semiconductors, [19][20][21] generally, selective solar absorption and high-temperature stability are not required for solar cells. In addition, fabrication of nanopyramid structures onto solar cells is usually expensive, and diffi cult to be scaled up.…”
Section: Doi: 101002/adma201501686mentioning
confidence: 99%
“…[ 16,17 ] In an attempt to improve the performance of nanowire solar cells, it was also discovered that a conformal dielectric shell structure can increase the optical absorption and scattering of the semiconducting nanowire core when the dielectric shell has a lower refractive index than that of the semiconductor core. [ 18 ] Moreover, studies of various shape-engineered nanostructures, such as trapezoidal, [ 19,20 ] conical, [21][22][23] cross-sections, resulting in enhanced absorption effi ciency. [ 3,5 ] An interesting feature of the fi ndings is that the diameter-modulated silicon nanowires exhibit the stronger and more closely spaced resonance peaks in the absorption spectrum compared with the simple cylindrical nanowires.…”
Section: Doi: 101002/adma201505144mentioning
confidence: 99%
“…Despite the antennaeffect-mediated strong absorption at short wavelengths, the overall performance of SNSCs is still far from expectation due to the narrow resonant bands and the relatively low absorption at long wavelengths. To improve the lightharvesting performance, properly engineering the structure parameters and cross-sectional morphology of the nanowires has been widely discussed in recent literatures [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. It was shown that the light absorption in nanowire devices could be effectively engineered through control over the size, geometry and orientation of the nanostructure [8].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the light absorption in nanowire devices could be effectively engineered through control over the size, geometry and orientation of the nanostructure [8]. For instance, metal-core/semiconductor-shell nanocones were proposed and a broadband solar absorption enhancement was predicted by finite-difference time-domain (FDTD) simulation [9]. A dielectric core-shell design could work as an efficient optical antenna for solar incidence [10].…”
Section: Introductionmentioning
confidence: 99%